2000
DOI: 10.1021/cg000009c
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Polymorphism as a Probe for Molecular Self-Assembly during Nucleation from Solutions:  The Case of 2,6-Dihydroxybenzoic Acid

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 21 publications
(39 reference statements)
5
151
0
4
Order By: Relevance
“…This has been reported in the growth of 2,6-dihydroxybenzoic acid (35). It was found that carboxylic acid dimers were present predominately in toluene from which a dimer-based crystal form was produced, while polymeric aggregates appeared to dominate in chloroform, leading to a hydrogen-bonded catemer observed in the harvested crystal structure.…”
Section: Introductionsupporting
confidence: 57%
“…This has been reported in the growth of 2,6-dihydroxybenzoic acid (35). It was found that carboxylic acid dimers were present predominately in toluene from which a dimer-based crystal form was produced, while polymeric aggregates appeared to dominate in chloroform, leading to a hydrogen-bonded catemer observed in the harvested crystal structure.…”
Section: Introductionsupporting
confidence: 57%
“…How the solute is dominantly present in solution could thus strongly influence the crystal nucleation process. It was for instance reported that 2,6-dihydroxybenzoic acid 11 associates into dimers in toluene and catemers in chloroform. Crystallization from these solvents leads to the dimer crystal structure form 1 in the case of toluene and to the catemer crystal structure form 2 in the case of chloroform.…”
mentioning
confidence: 99%
“…To model the graphite surface, we employed a large cluster consisting of two graphitic layers, each containing 20 20 unit cells. For the muscovite mica surface, we employed a 8 4 unit cell cluster measuring approximately 34 40 2 and assigned ionic charges to all atoms (Al +3, Si +1, O surface À0.75, O interior À1, K +1, where the oxygen subscripts refer to their position in the mica slab) to be of consistent magnitude with other similar theoretical studies. [19] Although real muscovite mica corresponds to a blend of interlayer cations, only potassium surface cations were considered here for simplicity, with half of them removed from the external surface at random to ensure charge neutrality.…”
Section: Methodsmentioning
confidence: 89%
“…To control the formation of these self-assemblies it is therefore fundamental to study not only the molecule-molecule interactions but also the interactions of the molecule with the solvent and with the substrate. [2] Due to their structural and electronic characteristics, tetrathiafulvalenes (TTFs) have been the center of attention as a source of building blocks for the preparation of materials with interesting electrical properties. [3] TTFs have been used successfully for a large variety of purposes, such as preparing a multitude of conducting charge-transfer salts, [4] molecular wires, [5] donor-acceptor dyads, [6] ionic sensors, [7] molecular machines, [8] and organic field-effect transistors.…”
Section: Introductionmentioning
confidence: 99%